IMAGE FUSION BASED ON PRINCIPLE COMPONENT ANALYSIS AND WAVELET TRANSFORM - Yogesh V.Chandratre, Rajesh.R.Karhe (International Journal of Research Science and Management, 2015)
Image fusion is important method which is employed invarious fields such as biomedical, remote sensing, robotics, different medical applications. In this technique two or more images generated from same or different image sources which may carry either same or different parameters of information these images are fused into unique integrated image which will improve accuracy as well as eliminates unwanted information. This image fusion techniques minimizes uncertainty and redundancy in output which maximizes relevant information in particular application.